"Pop Culture": Simplification of the Institute of Art - Даниил Петрович Фролов (Journal of Economic Sociology, 2010)
Transformation of music art into the type of entrepreneurship activity is unavoidable under the conditions of global capitalism formation, but artificial acceleration or slowdown of the dynamics of this process leads to the appearance of sharp reproductive disproportions in the sphere of entertainment with negative long-term effects.  The object of the study is one of the crucial segments of show business – pop culture. The latter is used in the context of the music art personalities. The goal of the paper is to underline the scientific rational understanding of the pop culture phenomenon under the prism of economic sociology and institutional economy.